Social costs of robbery and the cost-effectiveness of substance abuse treatment. - Basu, Anirban; Paltiel, A David; Pollack, Harold A (Health economics, 2008)
Reduced crime provides a key benefit associated with substance abuse treatment (SAT). Armed robbery is an especially costly and frequent crime committed by some drug-involved offenders. Many studies employ valuation methods that understate the true costs of robbery, and thus the true social benefits of SAT-related robbery reduction. At the same time, regression to the mean and self-report bias may lead pre-post comparisons to overstate crime reductions associated with SAT. Using 1992-1997 data from the National Treatment Improvement Evaluation Study (NTIES), we examined pre-post differences in self-reported robbery among clients in five residential and outpatient SAT modalities. Fixed-effect negative binomial regression was used to examine incidence rate reductions (IRR) in armed robbery. Published data on willingness to pay to avoid robbery were used to determine the social valuation of these effects. Differences in IRR across SAT modalities were explored to bound potential biases.All SAT modalities were associated with large and statistically significant reductions in robbery. The average number of self-reported robberies declined from 0.83/client/year pre-entry to 0.12/client/year following SAT (p<0.001). Under worst-case assumptions, monetized valuations of reductions in armed robbery associated with outpatient methadone and residential SAT exceeded economic costs of these interventions. Conventional wisdom posits the economic benefits of SAT. We find that SAT is even more beneficial than is commonly assumed.
Keywords: Adolescent; Adult; Cohort Studies; Cost-Benefit Analysis; Female; Health Care Costs; Humans; Male; Substance Abuse Treatment Centers; Substance-Related Disorders; Theft